Comparative transcriptomic analysis and genome-wide identification provide insights into the potential role of fungal-responsive MAPK cascade genes in tanshinone accumulation in Salvia miltiorrohiza - Abozeid, Ann; Du, Xinru; Zhang, Lan; Yang, Furui; Wu, Jianxiong; Zhang, Lin; Cui, Qi; Yang, Zongqi; Yang, Dongfeng (Frontiers in Plant Science, 2025)
Salvia miltiorrhiza is a well-known traditional Chinese medicine (TCM) for its bioactive tanshinones that are used to treat various diseases and have high antimicrobial properties. Previous studies have shown that tanshinone accumulation in S. miltiorrhiza was shown to be significantly induced by fungal elicitors. Mitogen-activated protein kinases (MAPKs), which play critical roles in plant–microbe interactions and cellular processes, are known to regulate the accumulation of antimicrobial metabolites. In this study, we aimed to identify MAPK families in S. miltiorrhiza and screen SmMAPKs for candidates involved in fungal elicitor-mediated tanshinone accumulation. Through genome-wide analysis, we identified 17 MAPK, 7 MAPKK, and 22 MAPKKK genes in S. miltiorrhiza, which were distributed across nine chromosomes. Phylogenetic analysis classified SmMAPKs into two subgroups, TEY and TDY, similar to Arabidopsis MAPKs, while all SmMAPKKKs clustered under the MEKK subfamily. Cis-acting element analysis revealed that most SmMAPK genes are associated with stress and phytohormone responses suggesting their involvement in defense mechanisms. To investigate the role of MAPK s in tanshinone accumulation, hairy roots of S. miltiorrhiza were treated with two fungal elicitors, yeast extract and Aspergillus niger, for 1 and 4 days. HPLC analysis demonstrated that both elicitors significantly promoted the accumulation of tanshinones, particularly cryptotanshinone and dihydrotanshinone. Comprehensive transcriptomic analysis, followed by Pearson correlation coefficient analysis, revealed a strong positive correlation between tanshinone content and SmMPK4 and SmMPKK5, while negative correlations were observed with SmMPKKK6, SmMPKKK11, and SmMPKKK20. The presence of defense-related cis-acting elements in the promoter regions of SmMPK4, SmMPKK5, SmMPKKK6, SmMPKKK11, and SmMPKKK20 further supports their involvement in fungal elicitor-mediated tanshinone accumulation. This study provides critical insights into the regulatory roles of SmMAPK genes in tanshinone accumulation in S. miltiorrhiza in response to fungal elicitors. These findings have potential applications in enhancing tanshinone production for medicinal purposes offering a foundation for further research into the molecular mechanisms underlying tanshinone biosynthesis.